Ethical Considerations in Revision Rhinoplasty - Wayne, Ivan (Facial Plastic Surgery, 2012)
The problems that arise when reviewing another surgeon's work, the financial aspects of revision surgery, and the controversies that present in marketing and advertising will be explored. The technological advances of computer imaging and the Internet have introduced new problems that require our additional consideration.
Keywords: ethical; rhinoplasty; revision; internet